Declaration of debt by Max Bredig, September 11, 1937 - Bredig, Max Albert (1937)
Debt declaration by Max Albert Bredig (1902-1977). Starting in 1937, in order to emigrate from Germany, Jewish people had to have documents that certified they had no outstanding debts to the country. Other documents they needed were a passport, a formal dissolution of residence, approval from the Reich Ministry of Finance, and a customs declaration.
Keywords: Bredig, Max Albert, 1902-1977; Emigration and immigration; Jewish Holocaust (1939-1945); Finance, Personal; Third Reich